High‐resolution plant metabolomics: from mass spectral features to metabolites and from whole‐cell analysis to subcellular metabolite distributions - Kueger, Stephan; Steinhauser, Dirk; Willmitzer, Lothar; Giavalisco, Patrick (The Plant journal : for cell and molecular biology, 2012)
The main goal of metabolomics is the comprehensive qualitative and quantitative analysis of the time‐ and space‐resolved distribution of all metabolites present in a given biological system. Because metabolite structures, in contrast to transcript and protein sequences, are not directly deducible from the genomic DNA sequence, the massive increase in genomic information is only indirectly of use to metabolomics, leaving compound annotation as a key problem to be solved by the available analytical techniques. Furthermore, as metabolites vary widely in both concentration and chemical behavior, there is no single analytical procedure allowing the unbiased and comprehensive structural elucidation and determination of all metabolites present in a given biological system. In this review the different approaches for targeted and non‐targeted metabolomics analysis will be described with special emphasis on mass spectrometry‐based techniques. Particular attention is given to approaches which can be employed for the annotation of unknown compounds. In the second part, the different experimental approaches aimed at tissue‐specific or subcellular analysis of metabolites are discussed including a range of non‐mass spectrometry based technologies.